Outbreak of Type C Botulism in Backyard Poultry in Santa Catarina, Brazil - Quevedo, Lucas de Souza; Schmitt, Sara Elis; Withoeft, Jéssica Aline; Cristo, Thierry Grima de; Figueiredo, Camila Aparecida; Santana, Jordana Almeida; Silva, Rodrigo Otávio Silveira; Casagrande, Renata Assis (Acta Scientiae Veterinariae, 2022)
Background: Botulism is a disease caused by the ingestion of neurotoxin produced by Clostridium botulinum, characterized by flaccid paralysis, which can lead to high mortality. They have seven types of neurotoxins (A, B, C, D, E, F, and G) and, in birds, most cases are attributed to type C. They are considered sources of botulinum toxins where the decomposition of organic matter occurs, like stagnant water and rotting food. The main feature of the disease in birds is ascending symmetric flaccid paralysis. The present study aims to describe an outbreak of type C botulism in backyard poultry in the state of Santa Catarina, Southern Brazil. Case: A visit was made to the property with 160 backyard poultry with a history of high mortality in the municipality of Agrolândia, Santa Catarina. Clinical signs were characterized by paralysis of the pelvic limbs, neck and pendular wings, which progressed to death within 48 h. There was a mortality rate of 37.5% (60/160) between March and May 2019. These birds were kept in an overcrowded environment, with different species (chickens, ducks, teals, and turkeys) fed irregularly. The water supplied was provided from kitchen exhaust, accumulating in puddles on the floor that contained organic matter residues such as animal feces, food waste and bone fragments. The disposal of the carcasses of birds that died was in the same enclosure, buried superficially, facilitating the access of other birds to dig them up and consume them. Necropsy was performed on 2 chickens and one duck, no macroscopic or histopathological lesions were observed. Blood, liver, and gastrointestinal content samples were sent for research and identification of botulinum toxin through the serum neutralization test in mice. The presence of type C botulinum toxin was confirmed in the liver chicken of one sampled animals. Discussion: The identification of type C botulism toxin enabled the characterization of the outbreak, which is the toxin most associated with episodes of botulism in birds. It is not always possible to identify the origin of the infection, as intoxication can occur by ingestion of water contaminated with organic waste, however, in this outbreak, as sources of poisoning in birds, it was specified and occurred due to the ingestion of water with organic matter that was stagnant in the floor of the enclosure, and also by ingesting contaminated carcasses present in the area. In subsistence farming, botulism outbreaks are reported with greater frequency in the Northeast and Southeast of Brazil generally, cases in which sanitary conditions and incorrect carcass disposal favor the occurrence of the disease. As noted in the present study, high mortality is a common feature of botulism. The evaluated signs and developed evolution were similar to previous studies, which ranged from 14 to 72 h. The absence of macroscopic and histopathological changes is commonly reported in cases of botulism in domestic animals, since botulinum toxin only causes functional changes, with no tissue damage. The association of clinical signs, epidemiology, post mortem evaluation and detection of type C botulinum toxin concludes the diagnosis of botulism. Avian influenza and Newcastle disease are important diseases that have neurological conditions and high mortality that should be distinguished from botulism. This report confirms the need to associate history, clinical signs, absence of lesions with laboratory research for the diagnosis of botulism in birds. In addition, it reinforces the importance of disclosing basic management measures to prevent the occurrence of outbreaks such as presented in this report. Keywords: Clostridium botulinum, neurotoxin, bird disease, paralysis. Descritores: Clostridium botulinum, neurotoxina, doença de ave, paralisia.